(untitled) (Fiep Bulletin - online, 2014)
Diabetes Mellitus disease is extremely prevalent in the population . The guided physical activity is an essential part of the treatment of diabetes and brings numerous benefits to the practitioner . However, it should be prescribed and monitored by a qualified professional with knowledge of the pathophysiology of diabetes , but also and especially on physical assessment , exercise physiology , and physical education ( sports, gymnastics , dance , recreation, etc. . ) . To guide and achieve the potential therapeutic benefits resulting from physical activity for diabetics it is necessary extensive knowledge in exercise metabolism , diabetológica therapeutic modalities and options for practices , and didactic- pedagogic training . Thus , the professional indicated to prescribe and monitor physical activity with diabetes , regardless of type, especially with regard to guidance, to be Professor of Physical Education specifically qualified to do so . We conclude that the effects provided by the regular practice of physical exercise for individuals with NIDDM , retains the known effects for non-pathological cases , and particularly when we put the physiological effects , they always end up being related to glycemic control .